Analisis Kinerja Aparatur Sipil Negara (ASN) Kelurahan Asam Kumbang Dalam Implementasi Program Bantuan Pangan Non-Tunai - Ardiansyah, Ardiansyah; Batu Bara, Beby Masithoh (PERSPEKTIF, 2025)
This study aims to analyze the performance of employees at Asam Kumbang Village in implementing the Non-Cash Food Assistance (BPNT) program based on five performance indicators proposed by Sedarmayanti (2017): work quality, punctuality, initiative, ability, and communication. The findings indicate that overall, the performance of civil servants in the village has been satisfactory. Employees can provide public services professionally, responsibly, and on time, although there are still technical obstacles such as delayed fund disbursement and incomplete beneficiary data updates. The employees demonstrate a high level of initiative in assisting unregistered residents eligible for aid, while their administrative and problem-solving abilities are considered adequate. Communication with the community is relatively effective, although improvement is needed in information dissemination. Supporting factors include leadership support, teamwork, and positive community response, while inhibiting factors include limited human resources, inaccurate data, and technical constraints in distribution. Overall, the performance of Asam Kumbang Village employees reflects good professionalism but still requires improvement in data accuracy and communication effectiveness.